Pengaruh Pembelajaran Berbasis Proyek dengan Portofolio terhadap Penguasaan Konsep Angiospermae dan Sikap Siswa SMA terhadap Sains - Fauzia, Iva Siti; Diana, Sariwulan; Kusnadi, Kusnadi (Department of Biology Education, Universitas Pendidikan Indonesia, 2018)
The purpose of this study was to analyze the effect of project-based learning (PjBL) with the portfolio towards mastery of the concept of Angiospermae and attitudes of high school students towards science. This study was conducted in one of the state high school in the city with a population that is used is a class X. The sample used in this study is one class with 38 students as sample number. The method used is pre-experimental design with pretest and posttest design. The concept of student mastery Angiospermae measured using about pretest and posttest which refers to the Revised Bloom's Taxonomy. Students 'attitudes toward science was measured by using a Likert scale questionnaire-4, the indicators used refer to the PISA 2006 results showed the achievement scores of N-gain students' mastery of concepts of 0.69 and including medium category. For the students' attitudes toward science, the results showed the achievement scores of N-gain of 0.34 and including medium category. Furthermore, these two variables were tested correlations to see the relationship between students' mastery of concepts and attitudes towards science. Correlation test showed the value of r = 0.612 and a strong correlation category. The response of students to the activities of PjBL with the portfolio after measured using questionnaire responses of students to learning with Likert scale-4, including into either category. Based on the research, PjBL with portfolio has affected the mastery of Angiospermae concept and attitude toward science in senior high school student.